RESPONSIVENESS SKOR QUICKDASH SEBAGAI ALAT UKUR HASIL AKHIR TERAPI FRAKTUR KLAVIKULA SEPERTIGA TENGAH - , PERWIRA BINTANG HARI, Dr. Rahadyan Magetsari, Sp.OT., Ph.D., FICS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Introduction: Quick Dash questionnaire is a valid measure of health status useful in patients with a wide variety of upper-extremity complaints. It is sufficiently sensitive to reveal even small changes in function and become a standard for evaluating upper extremity complaints. This method is easy to perform and require a minimal amount of time for evaluation of large population group. QuickDASH has been translate in Indonesian language with good sensitivity and reliability. The responsiveness of Indonesian language Quick Dash instrument as outcome measure for midshaft clavicle fracture have not been investigated. Method: The study population was 200 patients with the diagnosis of midshaft clavicle fracture based on clinical and radiological criteria. The clinical design was a classic Cohort study with measures 3 month and 6 month after Operative or Non-operative therapy. The responsiveness was evaluated based on the effect size (ES) and the standardized response means (SRM). Result and Discussion: The Quick Dash Instrument showed ES of 02,09 and an SRM of 2,80.The Indonesian language Quick Dash Instrument is sensitive to detect minimal important clinical changing of midshaft clavicle fracture outcome.